Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen dalam Membeli Bouquet Bunga di Toko Nuansa Florist Sumbersari - Hidayah, Nur; Yasin, Moh (KUBIS, 2024)
Service quality is an important factor in increasing competitiveness. Consumer expectations are always changing all the time so the quality of service provided must also be adjusted. The aims of this research are: 1). To find out whether the factors of reliability, responsiveness, guarantee, empathy and physical evidence have a significant effect on customer satisfaction. 2). To find out which service quality factors have a more dominant influence on consumer satisfaction. Data collection techniques were carried out using observation, questionnaires, interviews and documentation. The population is 30 consumers. Meanwhile, the data analysis technique uses statistical analysis techniques, namely multiple linear regression. The research results show that: 1). Partially, the variable that has the most dominant influence on consumer satisfaction is the attention/empathy variable with a sig value of 0.000, followed by the responsiveness variable which has a sig value of 0.004 and physical evidence with a sig value of 0.041. 2). Simultaneously, it is known that the calculated F value is greater than the F table value (46.019 > 2.62), and the significance value (sig) = 0.000 is smaller than the value α = 0.05. This means that together, the variables of reliability, responsiveness, guarantee, empathy and physical evidence have a significant effect on consumer satisfaction. 3). Based on the results of the determination test, the R square value has a value of 90.2%. It means Consumer satisfaction which is influenced by the independent variable service quality consisting of reliability, responsiveness, assurance, empathy